Aike P. Rots, Shinto, Nature and Ideology in Contemporary Japan: Making Sacred Forests - Kimura, Takeshi (Journal for the study of religion, nature and culture, 2023)
Aike P. Rots, Shinto, Nature and Ideology in Contemporary Japan: Making Sacred Forests (New York: Bloomsbury Academic, 2017) pp., $42.95 (pbk), ISBN: 9781350105911.